Blank postcard of Myron’s Athena (Städtische Galerie im Städelschen Kunstinstitut Frankfurt am Main)
Blank postcard featuring an illustration of a statue of the goddess Athena, created by the early classical sculptor Myron (5th cen., B.C.). The artist cast the original sculpture in bronze with another figure of the satyr Marsyas. Both figures were erected on the Athenian Acropolis.
Keywords: Sculpture; Sculpture, Greek; Myron, active 5th century B.C.